Ground Reaction Forces and Stair Descent on ACL Reconstructed Trained Subjects - Bouchouras Γεώργιος; Tsiokanos Αθανάσιος; Sykaras Ευάγγελος; Mylonas Αργύριος (Inquiries in Physical Education and Sport, 2015)
The aim of the study was to compare the Ground Reaction Forces (GRF), between the healthy and the Anterior Cruciate Ligament ACL reconstructed knee of trained subjects during stair descent. Eight men were recruited to participate in this study. The surgical reconstruction of the ACL was held three months before the evaluation. The results showed that there are differences between the two knees. In the transverse plane the reconstructed knee had greater peak values compared to the healthy one during the support phase (8.93% B.W. vs 5.29% B.W., p<0.05). In contraction, the healthy knee tended to have greater peak values in the vertical plane, during the support phase, compared to the reconstructed one (105.82 % B.W. vs 111.72% B.W., p=0.06). It seems that increased instability, which may be due to the lower muscle activity, lead to the different kinetic pattern of reconstructed knee. Further investigations may help clarify the relationship between the reconstruction of the ACL and the dynamic characteristics of the knee joint in daily activities such as stair descent.